Feline lymphoma of the nervous system. Immunophenotype and anatomical patterns in 24 cases - Mandara, Maria Teresa; Domini, Alessia; Giglia, Giuseppe (Frontiers in Veterinary Science, 2022)
In this study 24 feline lymphomas of the nervous system growing in different anatomical patterns were immunophenotypically characterized. Ten tumors affected the spinal cord, 8 the brain, 4 the peripheral nerves; 1 involved both the brain and the spinal cord, and 1 both the brain and the optic nerves. Twenty-two tumors were primary lymphomas. The affected animals were of 8 years as a mean age. Tumors developed as an extra-axial mass (11 cases), intra-axial mass (6 cases), leptomeningeal lymphomatosis (3 cases) and neurolymphomatosis (5 cases). One of them expressed both leptomeningeal lymphomatosis and neurolymphomatosis patterns. Two intra-axial brain lymphomas showed an angiotropic pattern. The optic chiasm was the most involved site for neurolymphomatosis. Immunolabelling was performed using anti-CD3, CD20, CD79a, PAX5, MUM-1, CD56, and anti-CD44, antibodies. Twelve tumors consisted of B-cell lymphomas, and 6 of T-cell lymphomas. Two cases were double reactive lymphomas while two cases consisted in non-B non-T lymphomas. B-cell lymphoma affected animals of 6.4 years in mean age, while T-cell lymphoma affected older animals (11.1 mean age). Extra-axial tumors mainly consisted in B-cell lymphomas (8/11). Neurolymphomatosis expressed different immunophenotypes. Two leptomeningeal lymphomatoses expressed T-cell immunophenotype. One angiotropic lymphomas was of T-cell phenotype while the second consisted in plasmacytoid lymphoma. Two lymphomas of the optic chiasm were of B-cell phenotype. Both the plasmacytoid lymphomas expressed MUM-1 in >75%. All the cases, except one, were CD56-negative. CD44-expression confirmed a common malignant potential for all the anatomical patterns of nervous system lymphoma in cats.